Aquatic food resources in tropical Africa: a comprehensive analysis - Okon, Ekemini M.; Okocha, Reuben C.; Folowosele, Deborah O.; Oluwafemi, Precious T.; Falana, Babatunde M. (Frontiers in Sustainable Food Systems, 2024)
Aquatic food production holds great promise as a viable solution to tackle the pressing issue of meeting the protein requirements of the African populace. It plays a crucial role in food security and economic growth, especially in tropical Africa. With a fast-expanding population, there is a growing need for aquatic food sources to provide inexpensive protein and essential nutrients. Despite Africa's vast aquatic food source supplies and the importance of aquatic food in healthy and sustainable diets, several challenges hinder its full exploitation in the tropical African environment. This study, therefore, aims to assess the existing state of aquatic food resources in Africa, examine the nutritional advantages associated with these foods, and identify the problems that hinder their maximal utilization. The findings highlight the differences in aquatic protein consumption across various countries, emphasizing the importance of considering local factors when formulating nutritional interventions and policies. The comparison between the supply of protein from aquatic sources and land animals across African nations revealed a consistent trend of lower availability of aquatic protein. Africa, in particular, had relatively lower per capita consumption values of animal protein. The continent's average quantity of land animal food significantly surpassed the average aquatic food supply. This suggests a predominant reliance on land animal sources in African countries to meet dietary protein needs. This finding holds significant importance for policymakers, nutritionists, and stakeholders, highlighting the need for targeted strategies to improve protein accessibility in African countries. Moreover, it calls for attention to address any existing imbalances between the utilization of land and aquatic protein sources in the region.